2021
DOI: 10.1017/s0030605319000668
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the occurrence of negative interactions between people and crocodilians in Mexico

Abstract: Negative interactions between people and crocodilians have increased worldwide, but in Mexico there have been few systematic reports and no rigorous evaluation of this problem. We compiled information on negative interactions between people and the spectacled caiman Caiman crocodilus and American crocodile Crocodylus acutus from the Worldwide Crocodilian Attack Database for 1993–2018, and we investigated interactions in greater depth, through interviews with people in La Encrucijada Biosphere Reserve. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Crocodiles usually defend these sites, because they are "territorial " or "they are nesting" (Fisherman 7). These findings match the findings of Aranda-Coello et al (2016) and González-Desales et al (2021) who reported that the reproductive season of the crocodiles is the most dangerous period. This zoning indicates danger; nevertheless, it does not imply that fishermen avoid those sites, because they are known as places "where more fish can be found " (Fisherman 9).…”
Section: Strategies To Avoid Conflictsupporting
confidence: 92%
See 2 more Smart Citations
“…Crocodiles usually defend these sites, because they are "territorial " or "they are nesting" (Fisherman 7). These findings match the findings of Aranda-Coello et al (2016) and González-Desales et al (2021) who reported that the reproductive season of the crocodiles is the most dangerous period. This zoning indicates danger; nevertheless, it does not imply that fishermen avoid those sites, because they are known as places "where more fish can be found " (Fisherman 9).…”
Section: Strategies To Avoid Conflictsupporting
confidence: 92%
“…Data generation was carried out through participative workshops (Geilfus, 2002;Gerritsen, 2016) that took place from January to February 2021. The participants were members of the Sociedad Cooperativa de Producción Pesquera Laguna de Alcuzahue and non-associated fisherman from both Alcuzahue and Cuyutlán.…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Across their global range, crocodilians are frequently involved in negative interactions with people (Gonzalez-Desales et al, 2021). Such negative interactions appear to be increasing across Africa because of human population growth, which in some areas coincides with a recovery of crocodile populations (Aust, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Latin American and Caribbean countries, negative interactions between humans and crocodilians have increased by 39% between 2018 and 2020 (Pooley et al 2021b). This may cause fatal incidents involving humans (as documented in Colombia by Balaguera-Reina and Farfàn-Ardia 2018 and in Mexico by García-Grajales and Buenrostro-Silva 2019), and destruction of natural sites due to greater anthropogenic activity (González-Desales et al 2021). In Brazil, several anthropogenic activities threaten crocodilian populations, such as hydroelectric dams (Campos 2015), roads (Campos et al 2012), illegal hunting Da Silveira and Thorbjarnarson 1999;Mendonça et al 2016;Mourão et al 1996;Muniz et al 2021) and urbanization (Mascarenhas-Júnior et al 2018).…”
Section: Introductionmentioning
confidence: 99%